The Role of 'Aisyiyah Women in Social Contribution in Central Java in the Contemporary Era - Khairunnisa Hanifah; Mohammad Zakki Azani (Universitas Muhammadiyah Surakarta, 2025)
Objective: This study examines the contribution of 'Aisyiyah Women to social development in Central Java in the contemporary era, with an emphasis on their strategies, challenges, and adaptations in the fields of education, health, and economic empowerment.Methodology: A literature research approach was used to analyze the social contribution of 'Aisyiyah in Central Java in 2019-2025. Data is collected from a variety of sources, such as books, journals, and official reports. The analysis was carried out based on the theory of women's empowerment from Naila Kabeer and the theory of social change from Anthony Giddens, to disseminate the impact and transformation produced by the social contribution of 'Aisyiyah to women's empowerment and social change.Results: The findings of the study show that 'Aisyiyah in Central Java plays an important role in women's empowerment and improvement of community welfare through skills training programs, health initiatives, and educational services, especially through PAUD Bustanul Athfal (ABA). More than 15,000 women have participated in entrepreneurship training, which has had a significant impact on their economic independence. In addition, the organization also addresses social issues such as gender equality, health, and poverty through extensive service programs.Application/Originality/Value: This research highlights 'Aisyiyah's response to contemporary challenges such as globalization, technological advancements, and cultural change, stating that the organization's relevance is maintained thanks to its innovative strategies, including digital engagement and collaborative partnerships with government agencies. The results of this study provide valuable insights to understand the role of women's organizations in driving social change and women's empowerment in Indonesia.